Changes in objectively-measured physical capability over 4-year, risk of diabetes, and glycemic control in older adults: The China Health and Retirement Longitudinal study. (February 2022) - Qiu, Shanhu; Cai, Xue; Zheng, Peilin; Yuan, Yang; Xu, Ying; Jia, Lijing; Sun, Zilin; Wu, Tongzhi
Highlights: Increases in physical capability were not related to reduced risk of diabetes. Changes in physical capability showed no favorable joint association on diabetes risk. Changes in physical capability had no relationship with changes in FPG or HbA1c. Increases in walking speed and grip strength may ameliorate insulin resistance. Abstract: Aims: High physical capability reduces risk of diabetes, but the association of its changes with risk of diabetes and glycemic control is unclear in older adults. This study aimed to quantify their association. Methods: A total of 1, 667 participants without diabetes and aged ≥ 60 years from the China Health and Retirement Longitudinal Study were included and followed over 4 years. Physical capability was objectively measured at baseline and 4-year later. Logistic regression models were used to assess the association of changes in physical capability with risk of diabetes. Results: During follow-up, 160 participants developed diabetes. None of the changes in physical capability expressed in continuous scales or in tertiles was associated with risk of diabetes in unadjusted or adjusted models (all P > 0.05), and no favorable joint effects were observed. Changes in physical capability were not associated with changes in fasting plasma glucose or hemoglobin A1c. Yet increases in walking speed or grip strength were related to reduced metabolic score for insulin resistance (both P ≤ 0.03). Conclusions: Increases in objectively-measured physical capability were not associated with reduced risk of diabetes but may ameliorate insulin resistance in older adults. Studies with longer follow-up periods are required to confirm these findings.